COUNSELING SYSTEM INTEGRATED ON THE WEB UNIT COUNSELING SERVICES FOR THE DEPARTMENT OF INFORMATIC ENGINEERING AND COMPUTER FACULTY OF ENGINEERING, STATE UNIVERSITY MAKASSAR - Sanatang Sanatang; Jumadi M Parenreng; Irvanshah Irvanshah (Jurusan Pendidikan Teknik Elektro, 2024)
The aim of this research is to produce an integrated counseling information system on the web of the counseling service unit of the department of informatics and computer engineering, Faculty of Engineering, Makassar State University and find out the results of system testing using ISO 25010 with 8 testing aspects. This research is a type of software design research (software development) and uses a prototype design model with stages: gathering requirements, building a prototype, evaluating the prototype, coding the system, testing the system, evaluating the system, and using the system. The subjects of this research were students from the Department of Informatics and Computer Engineering, Makassar State University. Data collection instruments were carried out through validation test sheets, student response questionnaires, and system expert assessment instruments. The results obtained from this research are: (1) Functional suitability of the system created is 100%